A review on security challenges and features in wireless sensor networks: IoT perspective - Mohd Aboobaider, Burhanuddin; Mohammed Al-Khazraji, Ali Abdul-Jabbar; Ismail, Ronizam; Hameed, Mustafa Emad; Basiron, Halizah; Kareem, Ali Noori (Penerbit Universiti Teknikal Malaysia Melaka, 2018)
The Internet of Things is becoming a very promising paradigm with the extensive market adoption of the development of associated technologies, such as;cloud computing, near-field communications, wireless mobile networks, etc. This will expose the future direction of communication around the world. Wireless Sensor Networks together with the existing communication technologies are enabling the continuous integration of controlling and processing the functionality of the Internet of Things applications. Since Wireless Sensor Networks are typically deployed for gathering sensitive information from unattended or hostile environments, they are exposed for security attacks, which are strongly affecting the user privacy and the network performance. There are various security mechanisms and solutions for Wireless Sensor Networks that have been proposed in the previous works. Therefore, it is mandatory to give attention for its applicability and feasibility features in terms of related security challenges based on the Internet of Things perspectives. The purpose of this paper is to explore and show the influence of Wireless Sensor Networks security challenges within the perspective of the Internet of Things and its applications. Consequently, an exploration of the major and minor security requirements in the Wireless Sensor Networks has been made in this paper, accompanied by a classification of the available attacks and threats against these requirements. Finally,a discussion on the Internet of Things security issues and challenges in Wireless Sensor Networks is provided.